Implementation of Educational Interventions for Prevention Diabetic Foot Complications - Martuti Dwi Handayani; Fitrian Rayasari; Dewi Anggraini; Wati Jumaiyah; Uswatun Hasanah (GLOBAL HEALTH SCIENCE GROUP, 2024)
Diabetic Foot Care is primary prevention in diabetic foot management to prevent injury to the occurrence of wounds on the feet of people with diabetes mellitus. Objective: To prove that educational interventions can prevent chronic complications, namely diabetic neuropathy (motor, sensory and autonomic) or death of the nerves in the feet, often exacerbated by infection. Method: This study used the Quasi Experiment method with the One Group pretest and posttest design method . Data collection was carried out using NAFF (Nottingham assessment of Functional Footcare) and the Attitude instrument modified by the Knowledge, Attitude and Practice (KAP) questionnaire. Determination of the sample using the accidental sample method of 24 people in Type 2 Diabetes Mellitus patients. Results: This study showed an increase in value of 11.12 points on NAFF and an increase of 1.41 points on attitudes after educational interventions related to diabetic foot care were carried out from May 30, 2024 to June 7, 2024. Conclusion: Diabetic Foot Care Education Intervention has been proven effective in reducing complications in diabetic feet and can be used as an evidence-based intervention in preventive care of diabetic feet in patients with Diabetes Mellitus.